ANALYSIS OF THE CAUSES OF ALLERGIC DISEASES IN THE HUMAN BODY AND THE EFFECTS OF DRUGS USED AGAINST THEM (World Bulletin of Public Health, 2023)
This article contains information about the causes of allergic diseases in the human body
Keywords: Allergy; immunobiological; allergen